Extended Depth of Focus IOL Implantation in Patients with Previously Monofocal IOL Implantation in Contralateral Eye - К. B. Pershin; N. F. Pashinova; A. Iu. Tsygankov; E. A. Antonov; I. V. Kosova; L. V. Batalina (Oftalʹmologiâ)
Purpose: to analysis the results of combined implantation of non-diffractive IOL with extended depth of focus and injector preloaded monofocal IOL.Patients and methods. 82 patients (164 eyes) after bilateral or combined implantation of AcrySof IQ Vivity (n = 72) and Clareon (n = 92) IOLs (Alcon, USA) with a mean follow-up of 6.2 ± 1.9 (6–8) months were included. 20 patients (40 eyes) with bilateral AcrySof IQ Vivity implantation formed group I, and 32 patients (64 eyes) with Clareon IOL implantation (n = 32) followed by Acrysof IQ Vivity implantation in the second (n = 32) formed group II. The comparison group (III) included 30 patients (60 eyes) with bilateral Clareon implantation. In group I, emmetropia was planned in the leading eye and myopia of 0.5–0.75 D in the nonleading eye; in groups II and III, emmetropia was planned in both eyes.Results. There was an increase in UCNVA from 0.29 ± 0.08 to 0.62 ± 0.14 in group I and from 0.22 ± 0.04 to 0.59 ± 0.11 in group II, UCIVA from 0.21 ± 0.08 in group I to 0.84 ± 0.18 in   group II, UCDVA from 0.27 ± 0.09 to 0.92 ± 0.21 in group I and from 0.34 ± 0.10 to 0.89 ± 0.18 in group II during a maximum follow-up period of 6 months. There was an increase in BCNVA from 0.58 ± 0.04 to 0.68 ± 0.07 in group I and from 0.43 ± 0.04 to 0.64 ± 0.05 in group II, BCIVA from 0.55 ± 0.10 to 0, 91 ± 0.24 in group I and from 0.27 ± 0.04 to 0.7 ± 0.15 in group II, BCDVA — from 0.61 ± 0.12 to 1.0 ± 0.31 in group I and from 0.42 ± 0.09 to 0.9 ± 0.25 in group II. The differences between groups were not statistically significant (p > 0.1). In group III the values of UCDVA and UCIVA were significantly lower than in groups I and II (p < 0.05). Group I showed a decrease in spherical refractive equivalent from –2.50 ± 1.2 to –0.15 ± 0.59 in the follow-up period of 6 months, in group II — from –3.0 ± 1.2 to –0.25 ± 0.48, in group III from –1.75 ± 1.1 to –0.25 ± 0.41 (p > 0.1). When comparing the frequency of adverse optical phenomena between the groups, no significant differences were found (p > 0.1).Conclusion. For the first time in Russia, a comparative analysis of the results of EDOF and monofocal IOL implantation compared to bilateral EDOF IOL and monofocal IOL implantation in patients with presbyopia was performed. The absence of significant differences between the groups allows to justify the implantation of non-diffractive EDOF IOLs in paired eyes in patients with previously implanted monofocal IOLs who wish to reduce dependence on spectacle correction at intermediate and near distances.